The Role of Soft Skills in Mediating the Relationship between Risk Management Competency and Work Readiness - Zuhrohtun Zuhrohtun; Kunti Sunaryo; Sri Astuti; Heri Susanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to investigate the impact of soft skills in mediating the relationship between risk management competence and job readiness in students in Yogyakarta. The independent campus learning program is expected to be able to bridge students in preparing for their future. One of the curricula in universities, especially accounting majors, is related to understanding risk management competencies. This analysis is carried out on students majoring in accounting who have obtained lessons related to risk management. This study used random sampling through data collection. Warp PLS is used as an analysis model using path analysis. Organizational risk management, process risk management and standard risk management are the three components used in this study. This study provides empirical evidence that only process risk management can affect soft skills but cannot directly affect student job readiness but process risk management competencies can affect student job readiness if mediated by soft skills. This research provides input to universities to improve the soft skills of prospective graduates so that they have better job readiness